STRATEGI PEMASARAN DALAM MENINGKATKAN HUNIAN KAMAR DI UBUD PADA MASA NEW NORMAL : STUDI KASUS HOTEL THE SHALA UBUD - I Dewa Ayu Ari Pramesti; Ni Ketut Iswarini; Ida Ayu Sri Puspa Adi (JURNAL KEPARIWISATAAN, 2023)
The purpose of the study was to find out marketing strategies to increase room occupancy in Ubud during the new normal period. Based on the data analysis that has been carried out, the results of the marketing strategy have not been optimally implemented by The Shala Bali, because there are several indicators of the 7P marketing mix that have not been implemented optimally, namely product quality indicators where there are several room facilities that are still problematic, brand indicators that are not well known, indicators transportation, namely the lack of lighting at night, the villa distribution channel has not collaborated with offline travel agents, the personal selling indicators owned by the villa are less diverse, and the direct marketing and public relations indicators are not implemented. The people villa element does not yet have a Sales & Marketing department and elements of physical evidence The Shala Bali does not have adequate lighting at night and lacks ample parking space. However, there has been a good implementation of marketing strategies at The Shala Bali, namely indicators of product variety, product design, room size, service, good price list indicators, clear payment periods and requirements, indicators of locations close to tourist destinations in Ubud. and the process elements are good and CHSE certified.